Novel gamma-irradiated chitosan-doped reduced graphene-CuInS2 composites as counter electrodes for dye-sensitized solar cells - Yonrapach Areerob; Chaowalit Hamontree; Phitchan Sricharoen; Nunticha Limchoowong; Sakchai Laksee; Won-Chun Oh; Kongsak Pattarith (My University, 2022)
To address the issues associated with traditional counter electrodes, a novel gamma-irradiated chitosan-doped reduced graphene-CuInS 2 composite (Chi@RGO-CIS) was used as the counter electrode (CE).
Keywords: Auxiliary electrode; Gamma Irradiation; TiO2 Photocatalysis and Solar Cells